Assessment for learning: Espoused and enacted practices of Malaysian teachers - Sathasivam, Renuka V.; Samuel, Moses; Mohd Nor, Norjoharuddeen; Tee, Meng Yew; Leong, Kwan Eu (Universiti Putra Malaysia, 2019)
High stakes assessment practices have been the most common summative assessments in schools. To address the shortcomings of the summative assessments, Assessment for Learning (AfL) was introduced to provide learners more active feedback and autonomy in their learning progression. In Malaysia, school-based assessments were introduced to reduce the dependency on summative assessments. This paper examines the espoused and the levels of enacted AfL practices of Malaysian Year 7 teachers. A survey and video research design was employed in this study where data were collected from a sample of teachers who taught Mathematics, Science, English Language, and Malay Language. To elicit teachers’ espoused AfL practices, a questionnaire was used while video recordings were utilized as a form of classroom observation to elicit teachers’ enacted AfL practices. The results indicated that there seemed to be agreement among teachers’ espoused AfL practices with AfL strategies for three dimensions which were Sharing Learning Target, Engineering Good Classroom Discussions, and Peer Assessment. The enacted AfL practices of these teachers were predominantly at the lowest levels for all dimensions of AfL practices. This study was not able to establish any relationship between the espoused and enacted AfL practices. It is suggested that both, espoused and enacted AfL practices were be brought to light as foundations for continuous improvement. It is hoped that these results would inform and influence policy makers about the future direction and decision making in improving the quality of school-based assessment implementation. © Universiti Putra Malaysia Press.